First Metatarsophalangeal Contact Properties Following Proximal Opening Wedge and Scarf Osteotomies for Hallux Valgus Correction: A Biomechanical Study. (April 2017) - Kia, Cameron; Yoshida, Ryu; Cote, Mark; DiVenere, Jessica; Geaney, Lauren E.
Background: Proximal opening wedge osteotomy (POWO) is an established procedure for moderate to severe hallux valgus. A common concern of this procedure is that it results in lengthening of the first metatarsal, which could cause increased intra-articular pressure of the first metatarsophalangeal joint (MTP) and may ultimately lead to arthritis because of these altered mechanics. The purpose of this study was to use a cadaveric model to compare intra-articular pressures and articulating contact properties of the MTP joint following either scarf osteotomy or POWO. Methods: Fresh-frozen cadaveric below-knee specimens with pre-existing hallux valgus (n = 12) and specimens without hallux valgus (n = 6, control group) were used. The hallux valgus specimens were stratified into 2 groups (n = 6 each): POWO or scarf osteotomy. The groups were matched based on the degree of deformity. Peak intra-articular pressure, force, and area were measured in all normal, preoperative, and postoperative specimens with a simulated weightbearing model. These measurements were made with a pressure transducer placed within the first MTP joint. Results: Postoperatively POWO group had slightly higher contact forces and pressures compared to the scarf group and lower contact forces and pressures than those of the normal group but were not statistically significant ( P > .05). Normal specimens had higher intra-articular force, pressure, and area than postoperative specimens but the difference was not found to be significant. First metatarsal lengthening was found in both the scarf and POWO specimens; however, neither increase was found to be significant ( P > .05). Conclusion: The results from this study show that after operative correction, contact properties of the fist MTP joint among normal, POWO, and scarf osteotomy groups revealed no significant differences. First MTP joints in those with hallux valgus had significantly lower contact force and pressure compared to those without hallux valgus. Clinical Relevance: With little long-term outcomes of proximal opening wedge osteotomy, this study will help predict the possibility of future MTP joint arthritis.